Understanding demand for, and feasibility of, centre-based child-care for poor urban households: a mixed methods study in Dhaka, Bangladesh - H. Elsey; F. Fieroze; R. A. Shawon; S. Nasreen; J. P. Hicks; M. Das; R. Huque; I. Hirano; H. J. Wallace; M. Saidur (BMC, 2020)
Abstract Background Centre-based child-care has potential to provide multiple health and development benefits to children, families and societies. With rapid urbanisation, increasing numbers of low-income women work with reduced support from extended family, leaving a child-care vacuum in many low- and middle-income countries. We aimed to understand perceptions of, and demand for, centre-based child-care in Dhaka, Bangladesh among poor, urban households, and test the feasibility of delivering sustainable centre-based child-care. Methods We used sequential mixed methods including a household survey (n = 222) and qualitative interviews with care-givers (n = 16), community leaders (n = 5) and policy-makers (n = 5). We co-produced and piloted a centre-based child-care model over ten-months, documenting implementation. A co-design focus group with mothers, parents' meetings, and qualitative interviews with child-care centre users (n = 5), non-users (n = 3), ex-users (n = 3) and staff (2) were used to refine the model and identify implementation issues. Results We found 24% (95% CI: 16,37%) of care-givers reported turning-down paid work due to lack of child-care and 84% (95% CI:74, 91%) reported wishing to use centre-based child-care and were willing to pay up to 283 Takka (~$3.30) per month. Adjusted odds of reported need for child-care among slum households were 3.8 times those of non-slum households (95% CI: 1.4, 10). Implementation highlighted that poor households needed free child-care with food provided, presenting feasibility challenges. Meta-inference across quantitative and qualitative findings identified the impact of the urban environment on child-care through long working hours, low social capital and fears for child safety. These influences interacted with religious and social norms resulting in caution in using centre-based child-care despite evident need. Conclusion Sustainable provision of centre-based care that focuses on early childhood development requires subsidy and careful design sensitive to the working lives of poor families, particularly women and must respond to the dynamics of the urban environment and community values. We recommend increased research and policy focus on the evaluation and scale-up of quality centre-based child-care, emphasising early-childhood development, to support low-income working families in urban areas.